Establishing the function relationship between time spectrum and proton range in proton therapy through Monte Carlo simulation - He, Yibo; Tong, Xin; Li, Yuhan; Cheng, Jingyi; Zhou, Rong (Frontiers in Physics, 2024)
To validate range shifts in proton therapy, we investigated the potential of using the temporal information of prompt gamma rays as an indicator. We simulated the proton transport process using Monte Carlo simulations and used a geometric scorer to obtain the location and timing of prompt gamma ray production. By using a homogeneous target material in the simulation model, we established a fitted relationship between the range of 90-210 MeV protons and the corresponding temporal spectral width. Additionally, by introducing air cavities of 2-20 mm in simulations of inhomogeneous target materials, we observed significant correlations between the range offsets and the temporal spectral widths. These correlations were fitted to derive a functional relationship between the two variables.